KARAKTERISTIK DAN UJI HEDONIK SABUN BERBAHAN LIMBAH AMPAS KOPI - Khoiroh, Iftitah Ummil; Setyo Andi Nugroho; Rosdiana, Eva; Asmono, Sepdian Luri; Novenda, Ika Lia; Pujiastuti (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2024)
Indonesia's coffee consumption is among the largest in the world, ranking 5th after Japan, which reaches 7.39 million. The growth of coffee shops corresponds with the increase in coffee waste, particularly coffee grounds, which are discarded, reaching up to 90% without being reused. Coffee grounds eventually become waste; thus, they are utilized as a material for soap making by recycling coffee grounds waste. The research aims to determine the hedonic test results or the preference level of soap made from coffee grounds waste. The hedonic test results will be calculated using a non-factorial Randomized Block Design (RBD) consisting of 4 treatments: P0 = control, P1 = 10 grams of coffee grounds, P2 = 25 grams of coffee grounds, and P3 = 50 grams of coffee grounds. The hedonic test results show that Hypothesis H1 is accepted for the most preferred color parameter, which is the P0 treatment with an average of 3.79b, the highest aroma average is the P2 treatment with 3.35b, the highest texture average is the P2 treatment with 4.29c, the highest foam quantity average is the P3 treatment with 3.99b, the highest moisture average is the P3 treatment with 3.93b, and the highest overall average is the P2 treatment with 3.99b because coffee grounds significantly affect the soap made from coffee grounds waste.